Pengembangan Bahan Ajar Penyajian Data Menggunakan Aplikasi Edmodo Di Kelas IV SD - putra, rizki pernanda; Ariani, Yetti; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract The purpose of this research is to extend teaching content, data presenter by using edmodo aplication, this research is an extending research with 17 people included as subject and gas been done at SDS Al-Azhar Bukittinggi. This extension research is conduct ini several step which are define, design, develop and disseminate. The total of all validation result is 80 which chategorized as sangat valid. Average percentage of practicality test using quistionnaire teacher's responses ia 89,28% which identified as sangat praktis. In the other hand student responses is 90,73% which identified as sangat praktis. Based on validation and practicallity result stated that teaching content which is being extend  is very valid and practical. As a conclusion, the extended teaching content using edmodo aplication on presentasion of data content on elementary school is identified as very valid and very practical. Key words: extention, teaching content, edmodo aplication.